Contrasting Roles of DOP as a Source of Phosphorus and Energy for Marine Diazotrophs - Filella, Alba; Riemann, Lasse; Van Wambeke, France; Pulido-Villena, Elvira; Vogts, Angela; Bonnet, Sophie; Grosso, Olivier; Diaz, Julia M.; Duhamel, Solange; Benavides, Mar (Frontiers in Marine Science, 2022)
The oceanic dissolved organic phosphorus (DOP) pool is mainly composed of P-esters, and to a lesser extent by equally abundant phosphonate and P-anhydride molecules. In phosphate limited ocean regions diazotrophs are thought to rely on DOP compounds as an alternative source of phosphorus (P). While both P-esters and phosphonates are well known to promote dinitrogen (N2) fixation, the role of P-anhydrides for diazotrophs is unknown. Here we explore the effect of P-anhydrides on N2 fixation at two stations with contrasting biogeochemical conditions: one located in the Tonga trench volcanic arc region (“volcano”, with low phosphate and high iron concentrations), and the other in the South Pacific Gyre (“gyre”, with moderate phosphate and low iron). We incubated surface seawater with AMP (P-ester), ATP (P-ester and P-anhydride) or 3polyP (P-anhydride) and determined cell-specific N2 fixation rates, nifH gene abundance and transcription in Crocosphaera and Trichodesmium. Trichodesmium did not respond to any of the DOP compounds added, suggesting that they were not P-limited at the volcano station, and were outcompeted by the low iron conditions at the gyre station. Conversely, Crocosphaera were numerous at both stations and their specific N2 fixation rates were stimulated by AMP at the volcano station and slightly by 3polyP at both stations. Heterotrophic bacteria responded to ATP and 3polyP additions similarly at both stations despite the contrasting phosphate and iron availability. The use of 3polyP by Crocosphaera and heterotrophic bacteria at both low and moderate phosphate concentrations suggests that this compound, in addition of being a source of P, can be used to acquire energy for which both groups compete. P-anhydrides may thus leverage energy restrictions to diazotrophs in the future stratified and nutrient-impoverished ocean.